Penyuluhan Hukum Pemahaman Kontrak Sederhana pada Masyarakat Desa Wisata Bumiwangi Kabupaten Bandung - Harrieti, Nun; Yuanitasari, Deviana (Universitas Pahlawan Tuanku Tambusai, 2025)
Bumiwangi Village, Ciparay District, Bandung Regency, is one of the tourist villages in West Java. Tourist villages are rural areas that have the potential for tourism development that focuses on the community and environmental conservation. Community understanding of basic contracts is very important, especially in its position as a tourist village. The method used in this community service is a community education method carried out through socialization and counseling activities. The results of this community service show that the majority of people have frequently seen basic contract. Understanding the legal requirements of agreements, including the types of agreements, is very important to know, including the essential elements of each contract made, especially buying and selling, renting, and cooperation. This understanding of basic contracts needs to be followed up with further community service with a focus on the practice of making basic contracts.